Basic and Brønsted Acidic Ionic Liquids as Catalysts in Biodiesel Synthesis (مجلة البحوث الأكاديمية, 2020)
In this article, use of some basic and Brønsted acidic ionic liquids for the purpose of synthesis of biodiesel has been reviewed. In such a technology, it is evident that use of ionic liquids in general is increasing. Ionic liquids can be tailored with respect to the desirable application. In-house-synthesized basic ionic liquids have sufficiently catalyze the transesterification reaction with an adequate biodiesel yield. Reusability, stable catalytic activity and use of moderate reaction conditions were all reported. Investigations deemed have shown that optimal reaction conditions have been demonstrated. In order to further promote the catalytic activity of a basic ionic liquid, immobilization of some metal chlorides in that basic ionic liquids has been proposed. Biodiesel contamination by metal residues as well as the possibility of release of HCl; however, have encouraged another arrangement. This arrangement relies on using an ionic liquid as a support for those readily available acidic/basic traditional catalysts. Via such an arrangement, high yield, low cost, reusability as well as simplicity of procedure were attained. Another success of ionic liquids as catalysts in biodiesel synthesis is that with the Brønsted acidic ionic liquids good product recovery can be ensured while biodiesel contamination with free molecules of the used catalyst can be prevented. In addition, good features of basic ionic liquids cited above have also been demonstrated while using those Brønsted acidic ionic liquids.
Keywords: Ionic liquid; basic ionic liquid; Brønsted acidic ionic liquid; synthesis